2009
DOI: 10.3109/09638280902874204
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of treadmill training for children with cerebral palsy

Abstract: The review suggests that treadmill training is safe and feasible for children with CP and indicates that there may be some positive benefits in walking speed over short distances and in general gross motor skills. The provision of PBWS may be particularly beneficial for children with more severe walking disability (GMFCS III and IV). Further research is necessary before it can be concluded that treadmill training is beneficial for children with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 30 publications
0
68
1
Order By: Relevance
“…The development of efficient and independent walking is an important therapeutic goal for many children with CP (Willoughby et al, 2009; Smania et al, 2011; Degelean et al, 2012; Graham et al, 2016). Given a positive effect of repetitive locomotor exercise on gait characteristics in children with CP (Smania et al, 2011), the rehabilitative protocol may further focus on improving the structure of the spinal locomotor output, e.g., by providing a feedback on the basic activation pattern burst durations.…”
Section: Discussionmentioning
confidence: 99%
“…The development of efficient and independent walking is an important therapeutic goal for many children with CP (Willoughby et al, 2009; Smania et al, 2011; Degelean et al, 2012; Graham et al, 2016). Given a positive effect of repetitive locomotor exercise on gait characteristics in children with CP (Smania et al, 2011), the rehabilitative protocol may further focus on improving the structure of the spinal locomotor output, e.g., by providing a feedback on the basic activation pattern burst durations.…”
Section: Discussionmentioning
confidence: 99%
“…18 In children with other chronic disorders, such programs have been implemented on a larger scale with positive effects on fitness and daily participation. [19][20][21] Looking more specifically at programs aimed to improve ambulation, treadmill training has shown promising results in other pediatric populations, 22 but there are some reservations because of methodological questions regarding study design and description of intensity and frequency of the intervention. 23 From a motor learning point of view and specificity of training effects, treadmill training is a task-specific training that allows repetitive practice of gait cycles, important for motor learning and neural plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Les é carts de force de ré action verticale par rapport au sol entre les membres en position debout, les paramè tres temporels-distance de dé marche et des dizaines de dimensions D et E de la mesure GMFM ont é té dé terminé s. Les participants ont pré senté une amé lioration statistiquement significative dans une mesure de GMFM (P < 0.01) et la valeur de ré partition du poids (P < 0.05), la vitesse de marche avant (P < 0.05) et la longueur de pas Introduction Achievement of efficient and independent locomotion with or without assistance is an important functional goal for many children with cerebral palsy (CP). Forward walking (FW) on a treadmill provides an increased opportunity to train the entire gait cycle, facilitating an enhanced gait pattern in both ambulatory and nonambulatory children with CP (Willoughby et al, 2009), and it has been shown to provide a range of benefits (Begnoche and Pitetti, 2007;Cherng et al, 2007;Dodd and Foley, 2007;Provost et al, 2007). Recently, some therapists have advocated backward walking (BW) on a treadmill or over ground in clinical practice to treat patients in rehabilitation for sports or functional mobility/gait.…”
mentioning
confidence: 99%